2014
DOI: 10.1186/s12967-014-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol exerts anti-hepatocellular carcinoma by microvesicle-mediated transfer of miR-142-3p from macrophage to cancer cells

Abstract: ObjectiveWe previously confirmed that propofol directly inhibited the viability, proliferation, and invasiveness of hepatocellular carcinoma cells in vitro. In this study, we investigated the mechanism underlying the anti-HCC effects of propofol.MethodsIn vivo antitumor activity was investigated in tumor-bearing mice following an intraperitoneal injection of propofol, with or without clodrolip. The co-culture system was used to verify that miR-142-3p was transported from macrophages to HCC cells. A miR-142-3p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 27 publications
2
82
0
Order By: Relevance
“…Microvesicles derived from liver stem cells inhibit HCC cell growth and this is mediated by various miRNAs contained in those microvesicles [31]. An intravenous anesthetic propofol has antitumor effects, and it has been shown that mice with propofol administration secrete macrophage-derived microvesicles and those microvesicles and their cargo miR-142-3p significantly inhibits tumor growth in vivo [32]. In liver cancers such as HCC, malignant cells can not only modify microenvironment to help their proliferation and invasion, but also be controlled by other cells via cell-cell communication using exosomes and microvesicles (Figure 4).…”
Section: Exosomes As Therapeutic Tools For Liver Diseasesmentioning
confidence: 99%
“…Microvesicles derived from liver stem cells inhibit HCC cell growth and this is mediated by various miRNAs contained in those microvesicles [31]. An intravenous anesthetic propofol has antitumor effects, and it has been shown that mice with propofol administration secrete macrophage-derived microvesicles and those microvesicles and their cargo miR-142-3p significantly inhibits tumor growth in vivo [32]. In liver cancers such as HCC, malignant cells can not only modify microenvironment to help their proliferation and invasion, but also be controlled by other cells via cell-cell communication using exosomes and microvesicles (Figure 4).…”
Section: Exosomes As Therapeutic Tools For Liver Diseasesmentioning
confidence: 99%
“…Previous studies have suggested that microRNAs (miRNAs) are involved in mediating the effects of propofol on anti-cancers, including miR-199a, miR-142-3p, miR-143 and let-7 (13)(14)(15)24,25). Propofol can influence the expression of these miRNAs, which in turn are able to regulate their target mRNAs to affect the behavior of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al investigated the effect of propofol on liver cancer and found that propofol can effectively inhibit the proliferation and invasiveness of HCC cells, and induce apoptosis, in vitro (13,14). In addition, Zhang et al demonstrated that propofol can inhibit tumor growth in tumor-bearing mice by activation of macrophages, thus exerting a therapeutic effect on HCC in vivo (15). However, the molecular mechanisms underlying the antitumor function of propofol on HCC has not been elucidated until now.…”
Section: Introductionmentioning
confidence: 99%
“…Animals bearing tumors were treated with anti-tumor propofol. The downregulation of miR-142-3p in TAMs using its inhibitor reversed the effect of propofol on hepatocellular carcinoma cells [166].…”
Section: Macrophage-derived Mirs-an Arm Of a Sentinelmentioning
confidence: 97%